Knowledge regarding Occupational Health Hazards among Nurses in a Hospital, Rupandehi, Nepal - Shrestha, Moonu; Karki, Srijana (Journal of Universal College of Medical Sciences, 2019)
INTRODUCTION: Health organizations are characterized by multidimensional and complex environment that makes nurses prone to occupational hazards and injuries. MATERIAL AND METHODS: A descriptive cross-sectional study was conducted to find out the knowledge regarding occupational health hazards among nurses. Sixty one respondents were selected as the study sample by using enumerative sampling method. Self- administered structured questionnaire was used to collect the data and collected data were analyzed by using descriptive and inferential statistics with SPSS software version 16. RESULTS: The findings of the study revealed that 70.5% of respondents had knowledge on meaning of occupational health hazards. Forty six percent had knowledge regarding meaning of biological hazards, 86.9% and 65.6% had knowledge on high risk person and immediate management for blood and body fluids exposure respectively. The finding of the study showed that 52.5% had high knowledge and 47.5% had low knowledge regarding occupational health hazards. There was statistically significant association between in-service training and respondents’ level of knowledge regarding occupational health hazard (p-value= 0.024). CONCLUSION: Based on findings of the study, it is concluded that more than half of the respondents have high knowledge regarding occupational health hazards. Besides this, respondents have high knowledge on meaning of occupational health hazards, causative agents of biological hazards, diseases that can occur after exposure to infected body fluids, preventive measures and low knowledge on meaning of biological hazards, virus having chance of transmission and first person to report after exposure to blood and body fluids.